1985
DOI: 10.1246/bcsj.58.2600
|View full text |Cite
|
Sign up to set email alerts
|

Free Radicals Produced from the Derivatives of Pyrylium Salts in Solution by Photoillumination

Abstract: The photoreactions of 2,4,6-triphenyl- (TPP), 2-t-butyl-4,6-diphenylpyrylium (2BDPP) and 2,4,6-triphenylthiopyrylium (TPTP) salts in tetrahydrofuran (THF) and/or 1,2-dimethoxyethane were investigated. Photoproducts were identified to be pyranyl radicals on the basis of photochemical behavior and ESR spectra. Quantum yields of one-electron reduction reactions of TPP, 2BDPP, and TPTP were obtained to be 0.21, 0.047, and 0.53, respectively. The hf coupling constants of protons in the radicals were determined by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 4 publications
3
15
0
Order By: Relevance
“…This hyperfine coupling (hfc) structure could be reproduced through simulation (Figure S15A) and was in complete agreement with previously reported hfc constants for that compound. 25 Moreover, the formation of 1b • was confirmed with UV–visible absorption spectroscopy (Figure S21A). 25b By contrast, no hyperfine splitting structure was observed for the analogous system containing 1a and 2a , even when a low-amplitude modulation was used ( M = 0.08 G).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…This hyperfine coupling (hfc) structure could be reproduced through simulation (Figure S15A) and was in complete agreement with previously reported hfc constants for that compound. 25 Moreover, the formation of 1b • was confirmed with UV–visible absorption spectroscopy (Figure S21A). 25b By contrast, no hyperfine splitting structure was observed for the analogous system containing 1a and 2a , even when a low-amplitude modulation was used ( M = 0.08 G).…”
Section: Resultsmentioning
confidence: 81%
“…25 Moreover, the formation of 1b • was confirmed with UV–visible absorption spectroscopy (Figure S21A). 25b By contrast, no hyperfine splitting structure was observed for the analogous system containing 1a and 2a , even when a low-amplitude modulation was used ( M = 0.08 G). 27 However, this absence of hyperfine structure was noted by Kawata and colleagues 26 and could be due to a broadening induced by the Heisenberg exchange effect.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In all cases, the major products are 4H-pyrans. The one-electron reduction of them when treated with zinc dust [24][25][26] in a degassed aprotic solvent gives the bichalcogenopyran derivatives via the pyranyl radical intermediates. We have previously described that the LiAlH 4 reduction of the 1-benzotelluropyrylium salts 11) and 1-benzoselenopyrylium salts, 14) the regioisomers of the title compounds, afforded a mixture of the corresponding 2H-and 4H-chromenes, respectively; the latter was the major product.…”
Section: Resultsmentioning
confidence: 99%
“…These bisisochromenyl compounds (3) would be produced by the homo-coupling of the radical intermediates. [24][25][26] Reaction of Pyrylium Salts with Nucleophiles We have recently found that both the 1-benzotelluropyrylium 11) and 1-benzoselenopyrylium salts 14) were attacked by a methoxide ion in MeOH to form the corresponding 4-methoxy-4H-chromenes as the major products in high yields. Although the telluropyrylium salts did not react with a secondary or tertiary alkoxide in the corresponding alcohol to give any characterizable products, the unsubstituted 1-benzoselenopyrylium salts 14) reacted with NaOi-Pr and KOt-Bu to afford the corresponding the 2-alkoxy-2H-selenochromenes in good yields.…”
Section: Resultsmentioning
confidence: 99%